Contending the Global Order: Singapore's Response to China's One Belt, One Road (OBOR) Initiative - Gan, She Hwa (2016)
The recent announcement of the OBOR Initiative could be hailed as China's next grand chess move in enhancing its rising stature in the world. As the hallmark of President Xi Jinping's epoch, the OBOR grand plan has far-reaching geopolitical, socioeconomic, military and security implications. [4th Award]-[Peer Assessment Review]